2007
DOI: 10.1016/j.febslet.2007.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The temperature activated HtrA protease from pathogen Chlamydia trachomatis acts as both a chaperone and protease at 37 °C

Abstract: Characterization of the protease, HtrA, from pathogen Chlamydia trachomatis is presented. The purified recombinant protein was a serine endoprotease, specific for unfolded proteins, and temperature activated above 34°C. Chaperone activity was observed, although this appeared target-dependent. Inactive protease (S247A) was able to chaperone insulin B-chain, irrespective of temperature, but at 30°C only HtrA and not S247A displayed significant chaperone activity for a-lactalbumin. These data demonstrate that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 29 publications
1
61
1
Order By: Relevance
“…In contrast, C. jejuni carries homologs of only HtrA and SurA and thus depends on these two chaperones for protein folding in the periplasm. A few bacterial HtrA homologs have been investigated in vitro, and these experiments have shown that HtrA is a bifunctional protein that, in addition to the chaperone activity, possesses proteolytic activity (24,28,63). In general, HtrA homologs are characterized by the presence of a trypsin-like serine protease domain and one or two PDZ domains that recognize substrates and activate the protease function (25,31).…”
mentioning
confidence: 99%
“…In contrast, C. jejuni carries homologs of only HtrA and SurA and thus depends on these two chaperones for protein folding in the periplasm. A few bacterial HtrA homologs have been investigated in vitro, and these experiments have shown that HtrA is a bifunctional protein that, in addition to the chaperone activity, possesses proteolytic activity (24,28,63). In general, HtrA homologs are characterized by the presence of a trypsin-like serine protease domain and one or two PDZ domains that recognize substrates and activate the protease function (25,31).…”
mentioning
confidence: 99%
“…CtHtrA activity was confirmed using ␤ -casein as a substrate [Huston et al, 2007] and confirmed to be purified to homogeneity by checking the preparations on Coomassie-stained SDS-PAGE. Protease assays using recombinant wild-type and mutant CtHtrA were performed as previously outlined in Huston et al [2011].…”
Section: Protease Activity and Specificity Assaysmentioning
confidence: 99%
“…CtHtrA was heterologously expressed and purified as previously described [Huston et al, 2007]. CtHtrA activity was confirmed using ␤ -casein as a substrate [Huston et al, 2007] and confirmed to be purified to homogeneity by checking the preparations on Coomassie-stained SDS-PAGE.…”
Section: Protease Activity and Specificity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were routinely cultured on Luria Bertani broth (LB) or agar plates (when appropriate) with ampicillin at 100 μg/ml. The wild-type htrA construct was previously described [32]. It was amplified using PCR and inserted into a pET-22b expression plasmid vector containing a C-terminal 6× histidine tag.…”
Section: Molecular Modeling and Refinementmentioning
confidence: 99%